2023
DOI: 10.1515/mt-2023-0092
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and antimicrobial activity of novel chitosan blended almond gum–nanosilica bionanocomposite film for food packaging applications

Ruby Thomas,
Vinaya Thattil Vincent,
Umapathy Manickam Janarthanam
et al.

Abstract: Almond gum and varied concentrations of nanosilica (0.2, 0.4, 0.6, 0.8, and 1.0 wt%) were introduced into the chitosan polymer matrix by solution cast method to enrich the characteristics of the bionanocomposite film. The surface topography, thermal stability, crystalline nature, and functional moieties of the synthesized bionanocomposite films were characterized by SEM, TGA, XRD, and FT-IR. The UV–Vis spectrophotometer showed a maximum absorption wavelength for the film containing the highest concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The rigidity and brittleness grew greater as flexibility reduced. Thomas et al [89] reported similar results; they observed that the elongation at break was significantly increased when almond gum powder was added to chitosan film at a concentration of 1.0 wt.%.…”
Section: Mechanical Propertiesmentioning
confidence: 67%
See 1 more Smart Citation
“…The rigidity and brittleness grew greater as flexibility reduced. Thomas et al [89] reported similar results; they observed that the elongation at break was significantly increased when almond gum powder was added to chitosan film at a concentration of 1.0 wt.%.…”
Section: Mechanical Propertiesmentioning
confidence: 67%
“…Figure 5 illustrates the SEM images of the chitosan and CS/MOP composite film at 1.0, 3.0, 5.0, and 10.0 wt.%. Figure 5A shows the dispersed, instead of uniform, morphology of the pure chitosan within the film [89]. The chitosan particles were dispersed across a sizable area at random intervals.…”
Section: Sem Analysismentioning
confidence: 99%